Quality of life among health care workers in Arab countries 2 years after COVID-19 pandemic - Ghazy, Ramy Mohamed; Abubakar Fiidow, Osman; Abdullah, Fatimah Saed Alabd; Elbarazi, Iffat; Ismail, Ismail Ibrahim; Alqutub, Sulafa Tarek; Bouraad, Etwal; Hammouda, Esraa Abdellatif; Tahoun, Mohamed Mostafa; Mehdad, Silmane; Ashmawy, Rasha; Zamzam, Abdulla; et al. (Frontiers in Public Health, 2022)
Background Assessment of the quality of life (QoL) among healthcare workers (HCWs) is vital for better healthcare and is an essential indicator for competent health service delivery. Since the coronavirus disease 2019 (COVID-19) pandemic strike, the frontline position of HCWs subjected them to tremendous mental and psychological burden with a high risk of virus acquisition. Aim This study evaluated the QoL and its influencing factors among HCWs residing in the Arab countries. Methods This was a cross-sectional study using a self-administered online questionnaire based on the World Health Organization QoL-BREF instrument with additional questions related to COVID-19. The study was conducted in three different languages (Arabic, English, and French) across 19 Arab countries between February 22 and March 24, 2022. Results A total of 3,170 HCWs were included in the survey. The majority were females (75.3%), aged 18–40 years (76.4%), urban residents (90.4%), married (54.5%), and were living in middle-income countries (72.0%). The mean scores of general health and general QoL were 3.7 ± 1.0 and 3.7 ± 0.9, respectively. Those who attained average physical, psychological, social, and environmental QoL were 40.8, 15.4, 26.2, and 22.3%, respectively. The income per capita and country income affected the mean scores of all QoL domains. Previous COVID-19 infection, having relatives who died of COVID-19, and being vaccinated against COVID-19 significantly affected the mean scores of different domains. Conclusion A large proportion of the Arab HCWs evaluated in this study had an overall poor QoL. More attention should be directed to this vulnerable group to ensure their productivity and service provision.